Towards inclusive communities : the right to water and sanitation for urban settlers in Cape Town, South Africa : a research project presented in partial fulfilment of the requirements of a degree of Master in International Development, Massey University, New Zealand - Zitye, Laxwell (Massey University, 2021)
The City of Cape Town is a fast-developing city facing challenges in rising informality. The city is challenged with basic service delivery and meeting water and sanitation needs of informal settlements where basic services are essentially urgent and a priority. Urban settlements’ dwellers find themselves deeply marginalised living in squalor and trapped in urban poverty. Access to water and sanitation is not always available in Cape Town even though it is a basic human right essential to sustaining lives and achieving a minimum standard of living of a socially acceptable level of wellbeing. This study focuses on the delivery of water and sanitation facilities to urban settlements. Specifically, it explores urban poverty and uses a rights-based framework of analysis to understand the issues surrounded by the City of Cape Town’s water and sanitation delivery policies. These basic needs are looked at in response to the rise of informal settlements’ water and sanitation needs. This study found that policy and development documents show increased and improved outcomes of basic service delivery interventions. However, these policies are not correlated with the realities on the ground. The provision of water and sanitation in urban settlements is articulated in policy documents as an act of assistance (a service) and not as a legal, morally ethical, or social responsibility (a right) deserved by settlers. Poor access to water and sanitation for informal settlements is therefore a consequence of profound inequalities in basic service delivery and a reflection of persistent urban poverty compounded by non-responsive national and local government policies. Essentially, this study shows the City of Cape Town has a long way to go to meet water and sanitation needs in informal settlements.